1, 3‐Dichloro‐2‐propanol induced ferroptosis through Nrf2/ARE signaling pathway in hepatocytes. Issue 10 (23rd July 2022) - Guan, Shuang; Zhang, Ranran; Zhao, Yanan; Meng, Zhuoqun; Lu, Jing
Abstract: 1, 3‐Dichloro‐2‐propanol (1, 3‐DCP) is a representative chloropropane environmental contaminant with multiple toxicities. Ferroptosis is a novel iron‐dependent form of regulated cell death that is closely associated with the accumulation of lipid peroxides, Fe 2+ and reactive oxygen species (ROS). In this study, we found that 1, 3‐DCP could induce mouse liver injury via ferroptosis. Administrating of C57BL/6J mice with 12.5, 25, and 50 mg/kg 1, 3‐DCP for 4 weeks via oral gavage, the data showed that 1, 3‐DCP exposure led to the pathological changes in mouse livers, remarkably induced accumulation of malondialdehyde (MDA) and Iron, reduction of glutathione (GSH), and changed in the expression of ferroptosis marker proteins glutathione peroxidase 4 (GPX4) and acyl‐CoA synthetase‐4 (ACSL4). Then, we also proved the results with HepG2 cells in vitro. The data showed that treatment 1, 3‐DCP significantly triggered the ferroptosis in vitro . Furthermore, we found that the ferroptosis‐related signal pathways were significantly activated in mice livers and HepG2 cells in response to 1, 3‐DCP exposure. The data showed that 1, 3‐DCP induced ferroptosis by inhibiting nuclear factor erythroid 2‐related factor 2 (Nrf2) translocation into nuclear and thereby suppressing the expression of its downstream target proteins including GPX4, ferritin heavy chain (FTH), ferroportin (FPN), cystine/glutamate transporter xCT (SLC7A11), and heme oxygenase 1 (HO‐1). Taken together, our findings confirmed that 1, 3‐DCP induced ferroptosis via the Nrf2/ARE signaling pathway in hepatocytes. Our works provide new toxicity mechanisms of 1, 3‐DCP with ferroptosis on hepatocytes injury.